A CRITICAL REVIEW ON HISTORICAL LINGUISTIC WRITTEN IN WIKIPEDIA - Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2012)
When does a languague begin? The truth is that it happens since the era of Aristoteles. Learning from those great philosophers’ era, we might want to know further about historical languages. The history wil tell about the issues related to the languages and also other factors deal with it. The language here is not only English but also other languages. The record prove that there are some languages had been extinct since there are no more native speakers of the language. Since the language is found, the science of it is developed. The development of linguistics occurred until now. There are many branches of lingusitics. There have been some changes too due to the linguistics. To find out more about what historical linguistics is, the writer tries to give critical for the article uploaded in Wikipedia about Historicl Linguistics. Key words : language, linguistics, historical linguistics